1994
DOI: 10.1046/j.1468-2982.1994.014003205.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Melatonin Excretion Throughout the Ovarian Cycle in Menstrually Related Migraine

Abstract: Nocturnal urinary melatonin excretion was significantly decreased throughout an ovarian cycle in 12 migraine without aura patients compared to 8 healthy controls. Normal increases in urinary melatonin excretion during the luteal phase was less pronounced in the migraine patients. Melatonin excretion was further decreased during headache. The data indicate impaired pineal function in migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 25 publications
0
43
1
1
Order By: Relevance
“…Transient or permanent alteration of the TSH surge has been described in hypercortisolemia (26), critical illness (27-30), postoperative recovery (31), hyperglycemia (32), chronic renal failure (33,34), depression (35-38), and aging (39). None of these was present in the children studied in this project.…”
Section: Discussionmentioning
confidence: 81%
“…Transient or permanent alteration of the TSH surge has been described in hypercortisolemia (26), critical illness (27-30), postoperative recovery (31), hyperglycemia (32), chronic renal failure (33,34), depression (35-38), and aging (39). None of these was present in the children studied in this project.…”
Section: Discussionmentioning
confidence: 81%
“…A phase shift in maximum melatonin levels was observed in 4 of 6 female sufferers of status migrainosus, compared to 9 controls [127]. Finally, a decrease in nocturnal urinary melatonin levels was reported in women suffering from migraine headaches related to their menstrual cycle [128,129].…”
Section: Can Melatonin Be a New Treatment For Migraine Headaches?mentioning
confidence: 84%
“…Serum melatonin levels are reduced in patients with cluster headache, particularly during a cluster period (Pringsheim et al, 2002). As regards plasma melatonin levels in migraine, the limited published data available derive from three small studies, the results of which suggested that female migraine sufferers have decreased nocturnal plasma melatonin levels both overall and during migraine attacks (Claustrat et al, 1989;Brun et al, 1995;Murialdo et al, 1994). Our study was not able to confirm these findings as we did not include a control group.…”
Section: Discussionmentioning
confidence: 68%
“…Since the pineal gland is considered to be a transducer of environmental stimuli into the neuroendocrine system, a pineal gland abnormality may be involved in headache etiology and homeostasis disruption. Levels of the pineal hormone melatonin have been found to be low in migraine (Claustrat et al, 1989;Murialdo et al, 1994;Brun et al, 1995) and in cluster headache (Leone et al,1995). Melatonin can act as a chronobiotic (being a circadian pacemaker of sleep) (Cajochen et al, 2003), an antioxidant, an antihypertensive, an anxiolytic and a sedative (Yousaf et al, 2010).…”
Section: Cognitive-motor Effects Of Treadmill Training In Pdmentioning
confidence: 99%